Impacts of the supplementation of açai lump flour in the diet of laying hens on productive performance, and fatty acid profiles and antioxidant capacity in the fresh and stocked eggs - Fortuoso B.F.* (2019)
© 2019 Wiley Periodicals, Inc.The aim of this study was to evaluate whether the supplementation with açaí flour in the feed of laying hens at the end of the production cycle has beneficial effects on the health and performance of the birds and on the quality of the eggs. Groups received basal diets supplemented with 0%, 0.25%, 0.5%, 1.0%, and 2.0% açaí lump flour. We observed better productivity linked to oviposition and egg mass in a dose-dependent manner. We also observed higher shell resistance in stored eggs and higher % albumen and peel in fresh eggs. Lower levels of lipoperoxidation were observed in fresh eggs (2.0%). In stored eggs, lipoperoxidation levels were lower in all supplemented groups. The antioxidant capacity levels in fresh or stored eggs was higher (2.0%). We also observed a higher content of monounsaturated fatty acids in the supplemented groups, whereas saturated fatty acids were lower in the egg yolks. Practical applications: Based on a regression analysis, we verified that 1.47% of açaí flour is ideal in terms of productive efficiency. Dietary supplementation with açaí flour improved performance, egg quality, and had positive effects on the health of hens. Supplementation with açaí flour increased egg shelf life, reducing lipid peroxidation, biochemical reaction responsible for egg putrefaction.